Data management aspects of public engagement with biodiversity documentation - Ortiz-Troncoso, Alvaro (PeerJ PrePrints, 2015)
Technological developments open up new opportunities for collaboration between biodiversity researchers and the general public. Three exemplary case studies were reviewed from literature: digitizing museum specimens, text-mining archived expedition journals and handling environmental monitoring data. Data management principles were applied to refine the ensuing requirements. Specific requirements were found to exist in three areas: collecting data, sharing data and improving data quality. Implications for data governance and quality control are discussed.
Keywords: crowdsourcing; text-mining; data integration; data policy; citizen science; data quality; environmental monitoring; digitization; primary biodiversity data; data governance